Jogo sério para simulação da técnica de entrevista no levantamento de requisitos de software - Rosa, Luis Henrique Carvalho (2018)
The requirement gathering is the stage that makes possible the definition of the restrictions and characteristics that the system must present, however, 85% of the failures in software development come from errors in this stage. Traditional approaches usually do not fully prepare the student for the job market, so an alternative and complementary approach to addressing these content is through more dynamic and experiential approaches such as gaming and simulation. With this premise, the game LevReq3D was developed, which is a serious game that simulates the experience of a professional in the area of Requirements Engineering. In this game, the student assumes the role of a requirements engineer of a software company involved in a project, in which he must elicit the requirements to develop an ordering system for a pizzaria. To carry out its task the student must interview the employees of the pizzaria and collect important information for the development of the system. For this, in the present work are implemented agents capable of making their presence perceived as real within the virtual world. Agents are also implemented with the concept of social interaction in order to make their interactions closer to those between humans, and their behavior can be altered according to the interactions carried out by the student. The results of this research point out that the game can fulfill its objective in assisting in learning the stage of requirement gathering software , mainly offering the possibility of practical experience of the application of the interview technique.